Utilização de cortinas de ar em espaços comerciais climatizados - Neto, Luís P. C. (2011)
This article give details about the techniques and methodologies used to study the influence of some geometric and dynamic parameters on Air Curtain effectiveness. Some results of technical inspections conducted in commercial establishments that use this kind of fence are presented and the energy and finance savings for open public acclimatized spaces is estimated.